THE EFFECT OF 70% ETHANOL EXTRACT FACIAL SPRAY GEL FORMULATION OF BANANA PEEL (Musa AAB) ON PHYSICAL PROPERTIES, PHYSICAL STABILITY AND ANTIOXIDANT ACTIVITY - faizah, mardiyati husna (Fakultas Farmasi Universitas 17 Agustus 1945 Jakarta, 2019)
Utilization of banana peel waste in cosmetics has not been done much. banana peel (Musa AAB) has good antioxidant activity to ward off free radicals. Antioxidants are more practical to use in the from of a facial spray gel. This research aims to know the effect of 70% ethanol extract facial spray gel formulation of banana peel (Musa AAB) on physical properties, physical stability and antioxidant activity carried out by DPPH free radical immersion method. Facial spray gel is made from extract concentrations of 4%, 6% and 8%. The results of the evaluation of physical properties showed that the higher the concentration of extract in the formulation would cause an increase in the valueof adhesion, pH and viscosity. but the value of the spraying pattern and pump delivery has decreased. Evaluation of physical stability showed that all formulas were stable at room temperature (25-27oC) with a storage period of 6 weeks. The results showed that the best antioxidant activity was found at extract concentration of 8% with IC50 value of 31.996 ppm.